Pengaruh Fraud Diamond terhadap Kecurangan Laporan Keuangan - Dewi Rizky Octariyanti; Muhammad Zaenuddin (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2022)
The purpose of this study is to find out how external pressure, ineffective monitoring, auditor turnover and director turnover affect financial statement fraud. quantitative approach is taken in the research method. A sample of 69 manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) in 2016-2018 became the focus of this study using secondary data. The Beneish M-Score model is used to measure the dependent variable, namely financial statement fraud, while the independent variables are external pressure, ineffective monitoring, auditor turnover and director turnover. Non probability sampling as a sampling technique and purposive sampling as a sampling technique. This study uses SPSS version 20 for logistic regression analysis as a data analysis technique. The test results show that financial statement fraud is influenced by external pressures, but is not affected by ineffective monitoring, auditor turnover and director changes.